Technical Aspects and Cost-Benefit of Fishing Business Using Purse Seine Fishing Gear at Ternate Fishing Port - Mutmainnah, Mutmainnah; Yuliana, Yuliana; Ahmad, Khamsiah; Surahman, Surahman; Najamuddin, Najamuddin; Mukminati, Mukminati; Edwarsyah, Edwarsyah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This study examines the development of the purse seine fishing business at Bastiong Fisheries Port in Ternate City regarding technical and cost-benefit aspects. Estimation of the level of business financial feasibility is analyzed using the Net Present Value (NPV) method, the Internal Rate of Return (IRR) method, and the Benefit Cost Ratio (B/C Ratio). The six fleets are KM. Lentera (1), KM. Nurwahidah (2), KM. Pratama Putra (3), KM. Ratu Rosari (4), KM. Salam Mesra (5), and KM. Qausar (6). The NPV, IRR, and B/C Ratio of each fleet are NPV 2,297,326,836 per year, a B/C Ratio 6 .6 per year, and an IRR of 52% per year for (1); the NPV value of 998,260,353 per year, B/C Ratio 3.5 per year, and an IRR of 49% per year for (2), the NPV value of 660,687,454 per year, B/C Ratio 2.6 per year, and IRR 50% per year for (3), the NPV value of 996,129,191 per year, B/C Ratio 3.5 per year, and IRR 35% per year for (4), the NPV value of 2,892,195,498 per year, a B/C ratio of 10.6 per year, and an IRR of 50% per year for (5). Number (6) has an NPV value of 809,122,892 per year, a B/C ratio of 3.5 per year, and an IRR of 56% per year, respectively.